Pré-condicionamento em sementes de Cassia excelsa Schrad - Jeller, Helma (Universidade Federal de São Carlos, 2002)
Cassia excelsa is a woody species commun in cerrado and srubland of brazilian northeast, known by cassia-do-nordeste . It could be used in landscape place and due to small size is used in street arborization, and could be recommended to recomposition of degradated areas. The aim of this work was to extend the knowlege about the ecophysiological behaviour, with the the study of priming in seed germination. For this purpuse, it was evaluated the effects of water and PEG solutions (-0,2; -0,4 and -0,6 MPa) in uptake process at 20ºC. The effects of the drying and storage after priming; the answer under water, thermic and salt stress after priming was also verified. Besides it, the priming effects in seed viability and vigor under optimal conditions (27ºC) were observed by eletrical conductivity, accelerated aging and submersion tests. In all the tests was used 4 replicates of 25 seeds, with daily evaluation, and considered germinated when radicle was > 2 mm long. According to the results of uptake curve of Cassia excelsa seeds was observed that with the decreased in the osmotic potential increase the time necessary to priming. At optimal temperature (27ºC) the answer of primed seeds was efficient if water or PEG solution at -0,2 MPa was used, and this answer is maintened after 15 days of storage at 5ºC, but the drying of the seeds overcome the positive effects of the pré-treatment. The priming in water or in PEG solutions increased germination percentage under water, salt and thermal stress, however, with restriction to germination rate. The electrical conductivity of the primed seeds in water or in PEG was reduced, constrated to the non-primed seeds, and increased in the dried seeds after the priming. The priming in water or PEG was efficiente to overcome the deteriorative process occurring in aging, in dehidrated and in moist seeds, after priming. The seed vigor of primed seeds was no affected by submersion in distilled water during diferents time periods.
Keywords: Sementes; Cassia excelsa; Germinação; Pré-condicionamento; Envelhecimento precose; Estresse hídrico; Secagem; CIENCIAS BIOLOGICAS::BOTANICA::FISIOLOGIA VEGETAL::ECOFISIOLOGIA VEGETAL